Difficulties that stand in the way of developing the laboratory environment in industrial vocational secondary education schools from the point of view of crafts teachers "A field study in Lattakia Governorate" - دويري رحاب; أحلام ياسين; صبا علي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the current research is to identify the difficulties that stand in the way of developing the laboratory environment in industrial vocational secondary education schools from the point of view of crafts teachers, and to identify the difference in the average scores of the sample members according to the gender variable and the variable of place. To achieve the goal: the descriptive approach was used, and a questionnaire was built to measure the difficulties, consisting of (300) items, and was applied to a sample of craft teachers in the schools of Lattakia for the academic year2022\2023.The survey amounted to( 24)male and female teachers, and through calculating Cronbach’s alpha, which reached and through half-partition, as the Spearman-Brown coefficient reached. The results showed that most of the challenges that stand in the way of developing the laboratory environment in industrial vocational secondary education schools existed at a medium and low degree, as the unfitness of the equipment and materials for use, weakness in basic installations such as water and electricity, and the availability of raw materials necessary for experiments came to a medium degree, with arithmetic means ranging between( 2.44)and(3.61)As for the location of the laboratory, it is suitable for student movement, and students are committed to attending the practical application. I suffer from a small number of classes for the practical side, which came with a low score, and arithmetic averages of less than(2.35) with the exception of courses for training in first aid, which came with a high score. With an arithmetic mean of( 3.96) . The results also showed that there were no statistically significant differences in the degree of difficulties that hinder the development of the laboratory environment due to the gender variable, there are statistically significant differences in the degree of difficulties due to the variable of place of residence(rural-city)in favor of individuals residing in the city.